A Review: A Comparative Study of Branded and Generic Anti-Hypertensive Drugs - Telrandhe, Anuksh; Phadnis, Ketakee; Dhoble, Nilakshi; Padole, Nitin; Baheti, Jagdish (Asian Journal of Pharmaceutical Research and Development, 2024)
This comprehensive review investigates the market landscape of antihypertensive medications, undertaking a detailed comparative analysis of branded and generic options. In the face of rising global prevalence of hypertension, the study aims to provide a holistic perspective on the efficacy, safety, and market dynamics shaping the use of branded and generic drugs in the management of these chronic conditions. Utilizing data derived from market trends, sales analytics, and consumer preferences, the review scrutinizes the market behaviors and forces influencing the adoption of branded and generic antihypertensive drugs. Factors such as cost-effectiveness, patient adherence, and healthcare provider preferences are explored to shed light on the complexities associated with medication selection in the context of chronic disease management. Through an in-depth examination of industry strategies, regulatory frameworks, and the role of healthcare policies, the review aims to uncover the interplay between market dynamics and clinical considerations. It seeks to inform healthcare professionals, policymakers, and industry stakeholders about the evolving landscape of choices in antihypertensive therapies, fostering a nuanced understanding that can guide optimal decision-making in patient care and resource allocation.